The Use of Mangosteen in Mousse No-Bake Cheesecake - Angie, Fionnie; Angie, Cernnie; Pakasi, Deandra; Situmorang, Jimmy (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Ampat Yogyakarta, 2024)
Mangosteen is a fruit that grows in tropical regions, commonly found in Indonesia. It has a unique sweet and tangy taste and holds numerous health benefits, making it a fruit often used for medical purposes. Mangosteen is rarely featured in dessert dishes, prompting this research with the aim of discovering a good combination of mangosteen in desserts and to introduce the mangosteen desserts to the generation Z. This research focuses on desserts originating from the European continent, specifically mousse and no-bake cheesecake. This research was conducted with organoleptic tests using hedonic test and hedonic quality test. The results and validity of the research are determined through class intervals and mean tests. It is hoped that this research can add insight into the discovery of the new flavors of European desserts, allowing people to enjoy desserts with new flavors. The results of the research are that mangosteen can be enjoyed in desserts which the sweet and tangy taste of the mangosteen makes a good combination in soft texture of mousse and the creaminess in no-bake cheesecake desserts.